2018
DOI: 10.1007/s00384-018-3176-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk of delayed bleeding after hemorrhoidectomy

Abstract: PurposeDelayed post-hemorrhoidectomy bleeding (DPHB) is a rare but serious complication. We investigated the incidence and risk factors of DPHB in patients undergoing hemorrhoidectomy using the LigaSure device or the Ferguson procedure.MethodsThis retrospective study included 382 consecutive patients with symptomatic grades II to IV hemorrhoids who received either LigaSure (184 patients) or Ferguson (198 patients) hemorrhoidectomy procedures. Thirty-two patients who experienced DPHB after discharge were follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
0
23
0
1
Order By: Relevance
“…Secondary haemorrhage usually arises as a consequence of infection in the haemorrhoidectomy wound and can occur between days 7 and 14 postoperatively. It affects approximately 5% of patients undergoing conventional haemorrhoidectomy [62]. Bleeding is often brisk and will require admission to hospital, fluid resuscitation, and examination under anaesthesia.…”
Section: Complications Of Haemorrhoidectomymentioning
confidence: 99%
“…Secondary haemorrhage usually arises as a consequence of infection in the haemorrhoidectomy wound and can occur between days 7 and 14 postoperatively. It affects approximately 5% of patients undergoing conventional haemorrhoidectomy [62]. Bleeding is often brisk and will require admission to hospital, fluid resuscitation, and examination under anaesthesia.…”
Section: Complications Of Haemorrhoidectomymentioning
confidence: 99%
“…It is possible that in our series energy devices were used in the more complex cases or for more extensive surgery, thus introducing a selection bias in favour of diathermy. A recent study by Lee et al [19] also showed that LigaSure devices increase the risk of delayed postoperative bleeding. They suggest that because LigaSure devices result in decreased postoperative pain and earlier return to normal activity, patients may be more likely to engage in physical activity at an earlier stage.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study by Lee et al . also showed that LigaSure devices increase the risk of delayed postoperative bleeding. They suggest that because LigaSure devices result in decreased postoperative pain and earlier return to normal activity, patients may be more likely to engage in physical activity at an earlier stage.…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of delayed postoperative haemorrhage has been reported to be 0.9-10%. 12 It is also seen that there is no difference in post-operative bleeding between haemorrhoidectomy done in elective and those done on an emergency setting.…”
Section: Discussionmentioning
confidence: 99%